2009
DOI: 10.1901/jaba.2009.42-595
|View full text |Cite
|
Sign up to set email alerts
|

Generality of the Matching Law as a Descriptor of Shot Selection in Basketball

Abstract: Based on a small sample of highly successful teams, past studies suggested that shot selection (two- vs. three-point field goals) in basketball corresponds to predictions of the generalized matching law. We examined the generality of this finding by evaluating shot selection of college (Study 1) and professional (Study 3) players. The matching law accounted for the majority of variance in shot selection, with undermatching and a bias for taking three-point shots. Shot-selection matching varied systematically f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 14 publications
6
53
0
Order By: Relevance
“…Using a laboratory choice task, Kollins, Lane, and Shapiro (1997) found that sensitivity often was lower for children with attention deficit hyperactivity disorder than for typically developing controls ( Figure 6A). Alferink et al (2009) found that the sensitivity of basketball shot selection was higher for regular college players than for substitutes ( Figure 6B). …”
Section: Quantitative Evaluation Of Modulating Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using a laboratory choice task, Kollins, Lane, and Shapiro (1997) found that sensitivity often was lower for children with attention deficit hyperactivity disorder than for typically developing controls ( Figure 6A). Alferink et al (2009) found that the sensitivity of basketball shot selection was higher for regular college players than for substitutes ( Figure 6B). …”
Section: Quantitative Evaluation Of Modulating Effectsmentioning
confidence: 98%
“…Applications of the generalized matching law (Figure 2) suggest that in many of these situations behavior allocation is a common function of relative reinforcement. Figure 3 shows the core matching relation as it describes conversation (Panel A; Borrero et al, 2007), basketball shot selection (Panel B; Alferink et al, 2009), and academic behavior (Panel C; Mace, Neef, Shade, & Mauro, 1994).…”
Section: Quantitative Evaluation Of Core Relationsmentioning
confidence: 99%
“…Quite often they are. For example, the GML has accounted for a large proportion of variance in basketball shot selection (two-point versus three-point field goals) when shot-making was considered as the reinforcer (e.g., Alferink et al 2009;Vollmer and Bourret 2000). It is convenient to refer to this kind of outcome as demonstrating the GML's reliability of fit.…”
mentioning
confidence: 99%
“…Reed et al (2011) found that emphasis on passing versus rushing (as measured through the GML's bias parameter) varied with the quality of defense played by opposing teams. In applying the GML to preference for two-point versus three-point basketball shots, Alferink et al (2009) found that the GML's sensitivity parameter differed for players on successful versus unsuccessful teams and for regular players versus substitutes. McDowell and Caron (2010) used the GML to describe verbal interactions between pairs of boys, with the relative frequency of two kinds of behaviors (statements that endorsed either rule-breaking or rule-following) considered as a function of the relative frequency of social reinforcement.…”
mentioning
confidence: 99%
“…A misunderstanding of this fundamental assumption has led several authors (i.e. Schroeder & Holland 1969;Conger & Killeen 1974;Schmitt 1974;Vollmer & Bourret 2000;Borrero & Vollmer 2002;Alferink et al 2009;McDowell & Caron 2010a, b) to conduct their analyses incorrectly. For instance, they used a small number of levels of the independent variable and pooled their subjects' data, which combined idiosyncratic dependent variables into a single analysis and did not account for within-subject and within-level variances.…”
mentioning
confidence: 99%